Role of axillary reverse mapping in decreasing complications after axillary dissection in breast cancer - Gaber, Ahmed; Fawzy, Ahmed; Sabry, Ahmed; El sisi, Alaa (International Surgery Journal, 2017)
Background: Breast cancer is one of the most leading causes of cancer deaths in female. Surgical treatment is considered the corner stone in its management. Axillary lymph node dissection (ALND) is an integral step in most of surgeries done, however it has many morbidities like prolonged seroma and lymphedema. Axillary reverse mapping (ARM) procedure was first described in 2007 in a trial to map the axillary lymphatics of the arm and avoid its injury therefore lymph complications. Methods: A prospective, randomized, controlled study over 72 female patients who underwent modified radical mastectomy (MRM). Patients were divided and randomized into study and control groups, thirty-six patients for each. In study group the ARM procedure was done by injecting 2.5 ml of methylen blue dye intra-dermally and subcutaneously in the upper inner ipsilateral arm along the medial intramuscular groove before ALND. Operative and post-operative results were recorded. Follow up was 6 to 24 months. Results: ARM procedure and successful visualization of arm lymphatics was achieved in 31 patients (86.1%). Statistically there was no significant difference between the two groups regarding patient and tumour characteristics, operative time and number of excised L.Ns. There was significant difference favouring the ARM group in decreasing the incidence of seroma (p= 0.040), lymphedema (p= 0.031) and time passed till remove drains (p <0.001). Conclusions: ARM procedure facilitated arm lymphatics visualization. It is easy non-time-consuming procedure. It resulted in significant reduction in incidence of seroma and lymphedema, with considerable reduction in the overall complications rate.